USE OF NUCLEAR PHYSICS METHODS FOR INVESTIGATION OF SHORT-RANGE ORDERING AND DEFECTS IN IRON BASED SIMULATUING ALLOYS - AIexander L Udovsky; Irene A. Evstukhina; Vladimir P. Kolotushkin; Victor Yu. Miloserdin V; Sergue G. Rudakov; Sergue V. Stepanov; Marina V. Cherkaschenko; Yury V. Funtikov (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Changes of short range ordering and electron density were investigated by nuclear gamma-resonance and positron annihilation methods in simulating alloys containing tungsten, chromium, molybdenum and vanadium, used as doping additions. Change of the short-range ordering parameter sign was detected in alloys containing vanadium as the doping element. Conditions for defects annealing were determined for Fe-9%Cr alloy.